The Appearance of Islam in India in Social and Religious Perspective: The Evolution of Religions and Tolerance in India (Journal of Advances and Scholarly Researches in Allied Education, 2022)
All these religions or rather sects derived their authority from the Vedas and consequently allwere dissoluble bound up with the existing caste system, for at that period it was practically, universally,though wrongly, believed that such hereditary caste was sanctioned by the Vedas. Also all of them wereremarkably tolerant towards each other except on occasions of heat and controversy. Buddhism andHinduism flourished side by side and Jainism too. In the same kingdom, in the same city, in the samefamily even, Hindus Jain and Buddhists lived peaceably, amicably holding discussion withoutembitterment on the most abstruse questions of man and god. If the father was devotee of Shiva, the sonwas devotee of Buddha and the same man in his own life might change his religion without causingdisturbance either in the family or the society. When this struggle between Buddhism and Brahmanismwas going on Islam made its appearance in India. Like the other religions with historical beginning. Itarose essentially as a spiritual movement meant to raise the believers morally and socially. But again, asin the case of the other religions it becomes unavoidably connected with politics and this very muchobscured its real nature and aspirations. It knew nothing of great religious dogmas and complicatedsystem of transcendental philosophy at first.